2023
DOI: 10.1007/s11605-022-05551-2
|View full text |Cite
|
Sign up to set email alerts
|

Liver Venous Deprivation Versus Portal Vein Embolization Before Major Hepatectomy for Colorectal Liver Metastases: A Retrospective Comparison of Short- and Medium-Term Outcomes

Abstract: Background Liver venous deprivation (LVD) is a recent radiological technique performed to induce hypertrophy of the future liver remnant. Medium-term results of major hepatectomy after LVD have never been compared with the actual standard of care, portal vein embolization (PVE). Methods We retrospectively compared data from 33 consecutive patients who had undergone LVD ( n = 17) or PVE ( n = 16) prior to a right hemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Five studies reported FLR percentage after embolization ( 21 , 23 26 ). This outcome was reported in 120 and 257 patients in the LVD and PVE groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies reported FLR percentage after embolization ( 21 , 23 26 ). This outcome was reported in 120 and 257 patients in the LVD and PVE groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported the operative time ( 21 , 23 , 25 , 27 , 28 ). This outcome was reported in 110 patients in the LVD group and 201 patients in the PVE group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow-up study of 10 patients, FLR percentage volume was increased up to 53.4% as early as 7 days following LVD [ 72 ]. Recent studies have further demonstrated the efficacy of LVD, even when compared to PVE alone or to ALPPS [ 73 , 74 , 75 ].…”
Section: Future Directions/goals To Enhance Future Liver Remnant Grow...mentioning
confidence: 99%
“…Some preliminary studies focused on the differences between PVE and LVD/eLVD, the degree of hypertrophy, postoperative complications, delay between embolization and surgery, but to our knowledge, none of them have compared the segmentary volumetry and the distribution of hypertrophy in the FRL [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%